Synthesis and characterization of novel ZnS/CeO2 nanocomposites - Wetchakun N. (2014)
Novel ZnS/CeO2 nanocomposite samples with different molar ratios were synthesized by the homogeneous precipitation method and hydrothermal method. The molar ratio of ZnS to CeO2 are 0.2:0.8, 0.4:0.6, 0.5:0.5, 0.6:0.4, and 0.8:0.2. Phase composition, crystallinity, crystal size, and morphology of novel ZnS/CeO2 nanocomposites were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy dispersive spectroscopy (EDS). The Brunauer, Emmett and Teller (BET) adsorption-desorption of nitrogen gas for specific surface area determination at the temperature of liquid nitrogen was performed on ZnS/CeO2 nanocomposites. The crystalline size of novel ZnS/CeO2 nanocomposites was found to be in the range of 5-10 nm with the corresponding BET specific surface areas in the range of 110-200 m 2/g. ©2010 IEEE.